Methods of the babesiosis modern diagnostics. quality cryterium. advantages and limitations (First report) - Pokhyl, S; Torianik І; Tymchenko О; Chygyrynska, N; Kostyria І (Annals of Mechnikov’s Institute, 2020)
Introduction. Babesia spp. is a tick-transmitted protozoan parasite, one of the causative agents of piroplasmosis (babesiosis). The disease is characterized by sings of malaise, inappetence, fever, hemolytic anemia and hemoglobinuria. The parasite has a wide distribution and occurs on all continents, except Australia. The life cycle of the parasite in animals organism (equine hosts, cattle, raveling dogs, cats) comprises two intracellular stages: sporozoites innoculated by infected ticks develop into schizonts within lymphocytes where they maltiply and subsequently transform into microzoites, which then invide erythrocytes. Purpose and tests wasto study theretrospective analysis of scientific reports about classic and modern microscopic and culture technique of blood smear staining. Materials and methodsThe objects of this investigations are the retrospective analysis of Ukrainian, European and pan American scientific papers (reports) about usingclassic and modern microscopic and culture technique of blood smear staining. Results of the study. As the result of the study (theoretic and patent literature analysis) it was revealed that the usedmicroscopic (by Romanovsky, Write, Papengaim, Nocht) and culture technique of blood smear staining in healthy domestic dogs and those ill with Babesia infection had certain advantages. This method is simple, undemanding, short-term and not labour-consuming; these features make it promising for use in field conditions of expeditions, etc. The method is reasonable for its pricing; the ingredients are actively used in research practice by Ukrainian scientists and widely represented on the domestic market. The presence of stains, which contrast by their wide colour spectrum, facilitates the integral awareness of the morphological plot of changes in studied tissues. From the technical viewpoint there are typical appeals of clear visualization in the structural differentiation of nuclei, cytoplasmic components and membrane. In conditions of analysis of blood preparations (smears), which belonged to control animals, the expressiveness and saturation of staining of blood cells, well-outlined borders of each of them and absence of any grey and blur in their contours were striking. Erythrocytes were bright braun, characterized by a round shape and presence of clarification in their centre (discocytes). Single sajes were well discerned; determination of their quantity was not a problem. The cytoplasm of leukocytes was notable for its gray and the nuclei for their violet-red tints. The colour of the granules was saturated, up to blue. The intracellular components were visualized, their differentiation was obvious. In case of observation of affected cells the qualitative properties of the stains remained unchanged. Erythrocytes were red-grey, with a well-outlined border and evident changes of the superficial architectonics (echino-, dacryo-, stomato-. ovalo- and microspherocytes). Poikilocytosis was rather strongly pronounced in 60 % of preparations, anisocytosis in 25 %. The phenomenon of formation of “coin columns” was more widespread than in controls. The intracellular inclusions were lilac and red-violet. The character of colour of the leukocyte population did not change. Some cases demonstrated numerous aggregations of thrombocytes in the immediate proximity to erythrocytes. These blood platelets were crimson, their granules (with different shape and size according to the degree of thrombocyte maturity) were notable for their dark blue tint. The revealed phenomena were attributed to pronounced adsorptive properties of the above stains against a background of absorptive ability of blood cells (connective-tissue ones according to typology) and the result of summation of the wide colour spectrum. Through diffusion of chemical components of the used stains facilitated long-term preservation of the preparations within the established period of observation as well as qualitative representation of major elements of cell structures and intracellular inclusions. Conclusions: investigations of the scientific reports about the declared technique (microscopic and culture) of staining of blood smears from domestic dogs and cattiehave been proved that is a qualitative, economically sound and technically available method of rapid diagnosis of haemoparasitic diseaseslike babesiosis.